Green Tea Polyphenol Epigallocatechin-3-Gallate-Stearate Inhibits the Growth of Streptococcus mutans: A Promising New Approach in Caries Prevention - Amy Lynn Melok; Lee H. Lee; Siti Ayuni Mohamed Yussof; Tinchun Chu (MDPI AG, 2018)
Streptococcus mutans (S. mutans) is the main etiological bacteria present in the oral cavity that leads to dental caries. All of the S. mutans in the oral cavity form biofilms that adhere to the surfaces of teeth. Dental caries are infections facilitated by the development of biofilm. An esterified derivative of epigallocatechin-3-gallate (EGCG), epigallocatechin-3-gallate-stearate (EGCG-S), was used in this study to assess its ability to inhibit the growth and biofilm formation of S. mutans. The effect of EGCG-S on bacterial growth was evaluated with colony forming units (CFU) and log reduction; biofilm formation was qualitatively determined by Congo red assay, and quantitatively determined by crystal violet assay, fluorescence-based LIVE/DEAD assays to study the cell viability, and scanning electron microscopy (SEM) was used to evaluate the morphological changes. The results indicated that EGCG-S was able to completely inhibit growth and biofilm formation at concentrations of 250 µg/mL. Its effectiveness was also compared with a commonly prescribed mouthwash in the United States, chlorhexidine gluconate. EGCG-S was shown to be equally effective in reducing S. mutans growth as chlorhexidine gluconate. In conclusion, EGCG-S is potentially an anticariogenic agent by reducing bacterial presence in the oral cavity.